Rencana Pemindahan Bandar Udara Eltari Kupang Strategi Perencanaan Kota Berkelanjutan - Yoseph Liem; L.M.F. Purwanto (Jurnal Lingkungan Karya Arsitektur (LingKAr), 2022)
Abstract: The challenge in urban planning is sustainability and sustainability so that it can support services for all citizens. The city of Kupang as one of the border cities with neighboring countries as well as a connecting city by land is currently growing. With the plan to develop an airport as a means of transportation, it can encourage economic growth and development in Kupang City. El Tari Kupang Airport needs to be fixed and improved both facilities, infrastructure and other supporting facilities through relocation. Oebelo Village in Central Kupang District, Kupang Regency is the right location of the other two places in West Kupang as well as other locations in East Kupang sub-district. With the plan to build a new airport, it will bring changes to the ecosystem of the surrounding area due to the increasing activity in the surrounding area. Changes will occur where the physical and economic changes in the area around the planned new Eltari airport in Oebelo and the extent to which these changes will have an impact on the socio-economic activities of the local community and the socio-cultural community. This result is expected to be an input for stakeholders and local governments in responding to developments in the socio-economic and cultural conditions of the local community.